Primary preventive interventions on traffic accidents among males: A review on the literature during 2009-2019 in Iran - Hosseini, Jalil; Khorasani-Zavareh, Davood; Abdoli, Mitra; Shariatpanahi, Samira; Lotfi, Samaneh; Nematollahi, Shahrzad (Archives of Men's Health, 2020)
Introduction: The present study aimed to compare the national health indicators and the effectiveness of primary preventive interventions on traffic accidents in Iran during the last decade (2009-2019). Methods: All published original articles on the primary preventive intervention and health indicators of traffic accidents in Iran were extracted. The inclusion criteria included epidemiologic studies on Iranian male population during 2009-2019. Data were screened and extracted by two independent evaluators and the quality of studies was checked using the STROBE checklist. The exclusion criteria included those articles aimed at presenting results of second or third levels prevention (including injury management, pre-hospital emergency management, economic analyses, case reports, and traffic accidents from non-human perspectives). Accident-related mortality rates, proportionate mortality from traffic accidents per 1000 vehicles, and per 1000 accidents were estimated. Results: A total of 65 original articles were included of which 13 were presented health indicators. The crude mortality rate varied from 57.1 in Sistan-Balooshestan province to 73 (per 100,000 population ) in Fars province. The age-standardized mortality rate among male pedestrians (per 100,000 population) varied from 10.6-33.4 in Gilan and Mazandaran, 42 in Fars, 50.9 in Lorestan provinces. During the last 10 years, the mortality rate decreased from 38 to 12 cases per 1000 vehicles and increased from 51 to 56 cases per 100 accidents. Studies on the effectiveness of primary level prevention have addressed regulations on controlling blood alcohol level and international projection models. Conclusions: The type of health indicators related to traffic accidents seems to vary greatly among studies. Investigation on the effectiveness of primary preventive interventions on traffic caccidents are proposed frequently by WHO. Nevertheless, short-term and long-term effectiveness of many interventions including educational packages, regulations and specific laws have not been assessed in Iran.